The effects of nutritional habits on leucite-based ceramic repaired with nanohybrid composites. Issue 15 (3rd August 2019) - Kazak, Magrur; Subasi, Meryem Gulce; Ozdas, Didem Oner; Zorlu, Sevgi; Cilingir, Aylin; Gunal, Solen
Abstract: The purpose of the present in vitro study was to evaluate the effects of nutritional habits (various liquids) on the color change and early repair bond strength of a leucite-based ceramic repaired with different contents of nanohybrid composite resins currently used by the clinicians. Ninety-six IPS-Empress CAD ceramic samples were obtained with low-speed diamond saw. For all samples same repair method was performed. Samples were divided into groups according to four nanohybrid composite resins used as a repair material: Tetric-N-Ceram Bulk Fill, Filtek Z550, Clearfil-Majesty Esthetic, Bisco-Aelite Aesthetic Enamel ( n  = 24). Composite resins were applied on ceramic surface and polymerized (40 sec). After waiting for 24 h, samples were divided into three subgroups according to liquid types: pomegranate-flavored mineral water, salad dressing, and distilled water ( n  = 8). Before and after immersion the samples in the various liquids, color measurements were calculated (24 h). Then, shear bond strength was tested with an universal testing machine.For the statistical analyses two-way ANOVA, Tukey HSD, Spearman's correlation tests were used at a significance of p  ≤ 0.05. Nanohybrid composites, liquids ( p  ≤ 0.001); correlation between nanohybrid composites and liquids ( p  ≤ 0.006) had statistically significant impacts on the color change values. Nanohybrid composites ( p  ≤ 0.017) and correlation between nanohybrid composites and liquids ( p  ≤ 0.004) had statistically significant impacts on the shear bond strength values. There was not any statistically significant correlation between color change and shear bond strength ( p  > 0.05). When a composite resin is selected as a repair material, nutritional habits of the patient should be taken into consideration. Although hydrophilic monomer type of a composite material is a more predominant factor associated with color change, filler weight has the same predominant effect on shear-bond strength.